Evaluation of genetic diversity, heritability and genetic progress in Kabuli type chickpea genotypes - Mojtaba Lotfi Aghmioni; mohammad Jaffar Aghaei; shahin vaezi; Eslam Majidi Heravan (پژوهش‌های حبوبات ایران)
To study breeding resource of Kabuli chickpea lines of National Plant Gene Bank of Iran, two separate experiments were conducted during 2010 and 2011. In this study, 57 lines of Kabuli type chickpeas- selected from primary evaluation experiments, out of 1500 accessions were planted at farm of Seed and Plant Improvement Research Institute in Karaj, Iran, according a randomized complete block design with three replications. All 57 lines were evaluated for different morphological and agronomical traits. Results showed high diversity for most of traits among accessions. Combined analysis of variance showed significant differences for years, genotypes and year × genotype interaction. Principal Coordinte Analysis resulted to four premier factors contributed around 85% of variations. Growth habit, number of flower and pod in plant, seed color, seed black dots and testa texture had higher coefficients in the first factor which contributed 59% of total variation. The yield components such as flowering duration, number of flower and pod in plant, number of pod per plant and number of seeds per pod showed high genetic diversity (21.58, 24.88, 52.51, and 27.01 respectively), and high heritabilities (93.49, 66.67, 94.72, and 82.86 respectively). So, these traits are suggested as most important indices for selection of superior chickpea line in breeding programs.